KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL PEMBELAJARAN VISUALIZATION, AUDITORY, KINESTHETIC (VAK) MENGGUNAKAN MEDIA PEMBELAJARAN VCD DAN CETAK - Bambang Dwi Atmojo; Selvi Riwayati (Jurnal Math-UMB.EDU, 2019)
ABSTRACTThe purpose of this study is to determine whether there is a difference in the ability to understand the mathematical problems of students through the VAK learning model using VCD and print learning media. This type of research is an experiment using pretest-posttest control design. The sample of this study were three classes, 2 experimental classes and 1 control class. The results showed that the average value of student learning outcomes through the VAK learning model using VCD learning media in the initial test was 46.31 while in the final test it was 83.56; the average value of student learning outcomes through the VAK learning model using print learning media (LKS) in the initial test of 37.31 while in the final test amounted to 72.21; and the average value of student learning outcomes through the conventional VAK learning model in the initial test was 45.34 while the final test was 55.5. The results of the values of these three classes were tested statistically using One way Anava at significant (Î± = 5%) to determine whether there were differences. From the results of the one way anava test there was a significant difference between the VAK learning model using VCD learning media, the VAK learning model using printed learning media (LKS), and conventional learning models.Â Keywords: Visualization, Auditory, Kinesthetic (VAK) Learning Models, Mathematical Problem Solving Capabilities, VCD Learning Media